PENGARUH MODIFIKASI JUMLAH ALUR DAN KECEPATAN PUTAR ROTOR BAR TERHADAP PRODUKTIVITAS DAN HASIL MESIN PEMECAH KEMIRI SISTEM RIPPLE MILL - Robert Sinaga; Julieta Christy; Donatus Dahang; Riduan Sembiring; Swati Sembiring; Seringena Br Karo; Daniel Gea; Relius Buulolo (Universitas Quality, 2022)
Advanced knowledge of candlenut deshelling machine is needed to obtain optimal whole round kernel. The objective of this study was to modify the rotor bar on a candlenut deshelling machine with a ripple mill system. The method was engineering or modification, were made in the form of processes and products. The number of grooves on the rotor bar was modified became 2, 4 and 6. Rotation speed of the rotor bar were varied to 15 rpm, 18.75 and 25 rpm. The number of grooves gave a very significant effect on the capacity of the machine, whole round kernel, broken kernel, sticky kernel and unbroken seeds. The rotational speed of the rotor bar gave a very significant effect on the capacity of the machine, broken kernel, and sticky kernel, and gave an insignificant effect on whole round kernel and broken kernel. Interaction between the number of grooves and the rotational speed of the rotor bar gave a very significant effect on the capacity of the machine and the sticky kernel and insignificant effect on the whole round kernel, crushed kernel and unbroken seeds.